Causes of Infertility among the Couples Who are Attending the Infertility OPD of BSMMU (Medicine Today, 2023)
Introduction: Infertility may be defined as inability to conceive within one year of unprotected regular coitus. Approximately 85 – 90% of healthy young couples conceive within 1 year, most within 6 months1. Infertility therefore affects approximately 10 – 15% of couples and represents an important part of clinical practice2. A general classification of causes of infertility are male 35 – 40%, female 40 – 50% (tubal 25%, ovulatory 20% and cervical 1 – 2%), sexual 10% and unknown 10%3. More than one factor per couple accounts for the total percentage appearing to exceed 100%.Objective: To assess the determinants of infertility among the infertile couples both male and female attending the outpatient department of infertility unit of the department of obstetrics and gynaecology of Bangabandhu Sheikh Mujib Medical University , Shahbagh, Dhaka.Materials & Methods: This prospective observational study was conducted in the Infertility unit, Department of Obstetrics and Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during the period from 01.07.2018 to 31.12.2021. Five hundred infertile couples were recruited from the out-patient department of infertility unit who came to take treatment for their infertility problem. Data were collected from the couples by data collection sheet and the data were plotted in the tables. The data were analyzed by SPSS program, version 28.Results: The socio-demographic characteristics of the study subjects (n = 500).Husbands age group was 22 -55in years, Mean ± SD (34.0 ± 5.9). Age of the female partners was 18 – 44 years, mean ± SD (27.1 ± 5.2). Majority of the female study subjects had secondary level of education (49.4%), where as in male study subjects secondary level of education was 30.4%, followed by graduates (29.6%). Occupation of female partners was mostly housewife = 395 (79.0%), occupation of male partners was mostly service = 356 (71.2%). Regarding religion, Muslims were 476 (95.2%), others were 24 (4.8%). Majority of them hailed from rural area (62%). According to BMI, majority of female were overweight (56%). Among the respondents, majority of them had primary infertility (59.8%) and the rest (40.2%) had secondary infertility. Regarding hormonal status of infertile women, most of them (94%) had serum FSH below normal (< 3U/L), serum LH below normal (< 2U/L) in 96% patients, Serum TSH above normal (>4.5 mU/L) in 49.0% patients, serum FT4 above normal (>21 pml/L) in (60.8%) patients, serum Prolactin level above normal (>630 mU/L) in 27.8) patients. Diabetes: In male = 28 (5.6%).Mumps: In male = 7 (1.4%). Chicken pox: In male = 18 (3.6%). Hypertension: In male = 10 (2.0%). Orchitis: In male = 6 (1.2%). Personal history of husband: Smoking = 129 (25.8%). In male patients, Testosterone level normal (10 – 30 nmol/L) in 133 (26.6%) patients and above normal (>30 nmol/L) in 367 (73.4%) patients. The semen analyses of the husbands of the infertile female patients shows, quality of semen poor (